Remediation of Diesel Fuel Contaminated Sandy Soil using Ultrasonic Waves - Wulandari P.S. (Civil Engineering Dimension, 2010)
Ultrasonic cleaning has been used in industry for some time, but the application of ultrasonic cleaning in contaminated soil is just recently received considerable attention, it is a very new technique, especially in Indonesia. An ultrasonic cleaner works mostly by energy released from the collapse of millions of microscopic cavitations near the dirty surface. This paper investigates the use of ultrasonic wave to enhance remediation of diesel fuel contaminated sandy soil considering the ultrasonic power, soil particle size, soil density, water flow rate, and duration of ultrasonic waves application.